Educational technologies in professional development of the land reclamation personnel in the context of digitalization - L. E. Pautova (Вестник университета, 2023)
The article analyzes the features of educational technologies for professional development of employees of reclamation organizations in the conditions of the educational and methodological center of additional professional education. The following general scientific research methods have been used: theoretical and practical analysis, development and systematization of information and analytical materials on professional training and development of employees of the Land Reclamation Department of the Ministry of Agriculture of the Russian Federation, logical and situational analysis, selective method in statistics, and result processing and generalization method. Relevant educational technologies for professional development of ameliorative industry workers and their gender-specific features, job categories, and stages of professional development that allow to determine significant changes in human resources of the industry have been identified for the first time. The features of implementation of promising areas of workers’ professional development in the reclamation industry of the agribusiness of the Ministry of Agriculture of the Russian Federation in the conditions of digital transformation have been revealed.